The Role Of Internal Communication In Improving Employee Engagement For Business - Mustari; Rijal, Syamsu (CITACONOMIA, 2025)
This study aims to analyze the effect of internal communication on employee engagement. Effective internal communication is believed to be able to increase employee engagement, which has a positive impact on productivity and work loyalty. This study uses the Systematic Literature Review (SLR) approach. The results of the analysis show that internal communication has a positive and significant effect on employee engagement. This study emphasizes the importance of open, clear, and two-way communication between management and employees to build high engagement in the work environment. The implications of this study encourage companies to strengthen internal communication channels and strategies in order to create a participatory and collaborative work environment.